Old Berrien Newsletters Vol 6. No.4. - Berrien County Historical Society (My University, 2024)
This document aims to provide historical context for the honoring of Confederate soldiers in Berrien County, Georgia. The author, a museum curator, asserts that monuments were erected to honor the lives and service of soldiers, not to celebrate enslavement. The document highlights that while some wealthy Georgians owned slaves, most Berrien County property owners in 1856 owned few or no slaves, and many men were conscripted into the Confederate Army regardless of their personal opinions on slavery or states' rights. Following the Civil War, Presidents Lincoln and Johnson, along with the U.S. Congress, implemented various amnesty acts and proclamations to restore citizenship rights to former Confederates, even posthumously pardoning figures like Robert E. Lee and Jefferson Davis. Ultimately, the document proposes adding a monument to enslaved individuals and their descendants on the courthouse square as a step towards reconciliation, rather than tearing down existing historical memorials.
This item contains 1 PDF with 4 pages in addition to 4 JP2 files
Keywords: Berrien County (Ga.); Berrien County Historical Foundation (Nashville; Ga.); Berrien County (Ga.)--History--Sources; Nashville (Ga.); Newsletters; Periodicals; Grady County (Ga.)--History; Historic preservation--Georgia--Berrien County; Electronic records